Preparation and application of a ZIF-67 derived Co2VO4 supercapacitor electrode material

By introducing V elements as the precursor template, the Co2VO4 material was prepared by using ZIF-67 as the precursor template, the problem of insufficient conductivity and ion transfer rate of ZIF material was solved, and the excellent electrochemical performance and efficient energy storage effect of supercapacitor electrode materials were achieved.

CN114121503BActive Publication Date: 2025-03-14XINJIANG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111301898.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-04
Publication Date
2025-03-14
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

The application of existing ZIF materials in the field of electrochemical energy storage is limited by their low conductivity and ion transport rate, making it difficult to achieve excellent electrochemical properties.

Method used

Co2VO4 material was prepared by introducing V elements using ZIF-67 as the precursor template, and a supercapacitor electrode material with excellent electrochemical properties was obtained by heat treatment.

Benefits of technology

It realizes the good electrochemical performance of Co2VO4 material in supercapacitor electrode materials, exhibits high specific capacity and good capacity retention, and is suitable for efficient energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114121503B_ABST
    Figure CN114121503B_ABST
Patent Text Reader

Abstract

The invention discloses a ZIF-67 derived Co2VO4 supercapacitor electrode material and a preparation method thereof. First, a mixed aqueous solution of a 2-methylimidazole aqueous solution, cobalt nitrate (Co(NO3)2·6H2O) and hexadecyltrimethylammonium bromide (CTAB) is prepared respectively; then, the 2-methylimidazole aqueous solution is added to the mixed aqueous solution, and after stirring, the precipitate is collected by centrifugation, and ZIF-67 is obtained after drying; the obtained ZIF-67 is ultrasonically dispersed in ethanol, mixed with an aqueous solution of ammonium metavanadate containing ammonia water, and a ZIF-67 derived Co2VO4 material is obtained after hydrothermal and nitrogen atmosphere calcination, and finally processed into a supercapacitor electrode material. The method is simple in process, green and environmentally friendly, and the prepared Co2VO4 material can maintain the original morphology of ZIF-67, and it will have excellent electrochemical properties when used as a supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of supercapacitors, and specifically relates to a ZIF-67 derived Co2VO4 material and a preparation method and application thereof. Background Art

[0002] The excessive use of non-renewable energy has led to global warming and other problems, which are becoming increasingly serious. At the same time, the intermittent nature of clean energy has seriously restricted its steady development. Developing efficient, stable and safe energy storage devices and improving the energy utilization rate of energy storage devices have gradually become one of the research and development directions of new energy. Supercapacitors (SCs), also known as electrochemical capacitors (ECs), not only have a higher power density than batteries and an energy density greater than traditional capacitors, but also have the characteristics of fast charging and discharging rates and long cycle life. Therefore, it is considered to be an energy storage device with great development potential. As an important component of supercapacitors, electrode materials directly determine the excellent electrochemical properties of supercapacitors.

[0003] Metal organic frameworks (MOFs) are a new type of porous material with a large specific surface area and unique pore structure. They are widely used in gas adsorption, catalysis, sensors and drug delivery. Zeolite imidazolate framework (ZIF) is a typical MOFs material with excellent thermochemical stability and is an excellent template material. However, due to the low conductivity and ion transmission rate of ZIF, its application in the field of electrochemical energy storage is limited. ZIF-67 is a material with Co element as the metal node and 2-methylimidazole as the organic ligand for alternating connection. It not only has the excellence of MOFs materials, but can also be made into transition metal vanadates by introducing multivalent V elements. When used as an electrode material, the material can exhibit very excellent electrochemical properties under the synergistic effect of Co and V. Summary of the invention

[0004] The purpose of the present invention is to propose a Co2VO4 material with excellent electrochemical properties derived from ZIF-67 as a precursor template, and to apply the Co2VO4 material to prepare supercapacitor electrode materials.

[0005] The specific implementation scheme for realizing the object of the present invention is as follows:

[0006] (1) 2-Methylimidazole was added to deionized water and stirred to obtain solution A; Co(NO3)2·6H2O and CTAB were dissolved in deionized water to obtain solution B; then solution B was quickly added to solution A and stirred for 0.5 h; after centrifugation and washing, the solution was dried at 60 °C under vacuum for 8 h to obtain a ZIF-67 precursor;

[0007] (2) ultrasonically dispersing the prepared ZIF-67 precursor in anhydrous ethanol to obtain solution C; dissolving NH4VO3 in deionized water to obtain solution D; adding solution D to solution C and continuously stirring to obtain a suspension;

[0008] (3) pouring the suspension obtained in (2) into a reaction vessel for hydrothermal reaction; washing by centrifugation, and drying at 60°C under vacuum for 8 h to obtain a reaction product;

[0009] (4) The obtained reaction product was heat treated under N2 atmosphere to finally obtain Co2VO4 material. The material was made into supercapacitor electrode material and subjected to three-electrode test. Under the current density of 0.5 A / g, the specific capacity of the supercapacitor was 281.13 F / g ~ 434.19 F / g. After 5000 cycles under the current density of 10 A / g, its capacity retention rate could reach 90.1%~95.1%.

[0010] Preferably, in the above step (2), the molar ratio of ZIF-67 to NH4VO3 is 1:1.5~2, for example, 1:1.5, 1:1.7, 1:1.9, 1:2.

[0011] Preferably, in the above step (2), the ultrasonic time of ZIF-67 is 10 to 30 min, for example, 10 min, 20 min, 25 min, 30 min.

[0012] Preferably, in the above step (2), the stirring time is 30 s to 3 min, for example, 30 s, 1 min, 2 min, 3 min.

[0013] Preferably, in the above step (3), the temperature range of the hydrothermal reaction is 90-150°C, for example, 90°C, 120°C, 150°C, 180°C.

[0014] Preferably, in the above step (3), the hydrothermal reaction time is 2 to 5 h, for example, 2 h, 4 h, 6 h, or 8 h.

[0015] Preferably, in the above step (4), the heating rate of the heat treatment is 2°C / min, and the calcination temperature is 250-450°C, for example, 250°C, 350°C, 450°C, 550°C.

[0016] Preferably, in the above step (4), the heating rate of the heat treatment is 2°C / min, and the calcination time is 1 to 4 h, for example, 1 h, 2 h, 4 h, or 6 h.

[0017] The Co2VO4 derived from ZIF-67 provided by the present invention can be used as a supercapacitor electrode material.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention prepares Co2VO4 material derived from ZIF-67 for the first time, and the material can maintain the original morphology of ZIF-67. The required raw materials are low in price and the preparation process is relatively simple and easy;

[0020] (2) The ZIF-67-derived Co2VO4 prepared by the present invention can inherit many advantages of ZIF-67, such as large specific surface area, multiple active sites, stable chemical properties, etc. The introduction of V can improve the defects of ZIF-67, such as poor conductivity. The Co2VO4 obtained by this method is made into a supercapacitor electrode material and exhibits good electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a field emission scanning electron micrograph of the ZIF-67 precursor prepared in Example 1.

[0022] Figure 2 This is a field emission scanning electron microscope image of the Co2VO4 electrode material prepared in Example 1.

[0023] Figure 3 This is the cyclic voltammetry curve of the Co2VO4 electrode material prepared in Example 1.

[0024] Figure 4 This is the constant current charge and discharge curve of the Co2VO4 electrode material prepared in Example 1.

[0025] Figure 5 This is the cycle stability curve of the Co2VO4 electrode material prepared in Example 1. DETAILED DESCRIPTION

[0026] The specific implementation steps of the present invention are further described below in conjunction with the accompanying drawings and technical solutions.

[0027] Example 1

[0028] This embodiment provides a method for preparing a ZIF-67 derived Co2VO4 material, comprising the following steps:

[0029] (1) 5.76 g of 2-methylimidazole was dissolved in 60 mL of deionized water to form solution A, and 874 mg of Co(NO3)2·6H2O and 15 mg of CTAB were dissolved in 30 mL of deionized water to form a uniform mixed solution B. Solution B was then quickly poured into solution A and stirred for 0.5 h. After centrifugation and washing, the solution was dried at 60 °C under vacuum for 8 h to obtain a ZIF-67 precursor.

[0030] (2) Disperse 50 mg of ZIF-67 precursor in 40 mL of anhydrous ethanol by ultrasonication for 20 min to obtain solution C; dissolve 44.56 mg of NH4VO3 in 10 mL of deionized water to obtain solution D; add solution D to solution C and stir for 1 min to obtain a suspension;

[0031] (3) The suspension obtained in (2) was poured into a 100 mL reactor and subjected to hydrothermal reaction at 120 °C for 4 h. The obtained product was washed by centrifugation and then dried under vacuum at 60 °C for 8 h.

[0032] (4) The reaction product obtained in (3) was heated to 350 °C at a heating rate of 2 °C / min under N2 atmosphere for 2 h to finally obtain Co2VO4.

[0033] Figure 1 is the field emission scanning electron microscope image of ZIF-67 obtained by (1), Figure 1 It can be seen that the prepared ZIF-67 is in the shape of nanocubes.

[0034] Figure 2 This is the field emission scanning electron microscope image of Co2VO4 obtained in (4). Figure 2 It can be seen that the prepared Co2VO4 maintains the nanocubic structure of ZIF-67, which also proves that ZIF-67 has good stability, and its surface roughness increases after the introduction of V.

[0035] The electrochemical performance test was carried out using three electrodes. 3 mol / L KOH was used as the electrolyte, Hg / HgO

[0036] The reference electrode is the platinum electrode, the counter electrode is the Co2VO4 electrode, and the working electrode is the Co2VO4 electrode. The preparation method of the working electrode is as follows: Co2VO4, acetylene carbon black, and PVDF are mixed and ground in a ratio of 8:1:1, and then coated on the nickel foam. Figure 3 and Figure 4 The cyclic voltammetry curve and constant current charge-discharge curve of Co2VO4 under three-electrode test are shown respectively. It can be seen from the figure that the electrochemical performance of Co2VO4 is good. At a current density of 0.5 A / g, the specific capacity of Co2VO4 can reach 434.19 F / g. Figure 5 This is the cycle stability curve of Co2VO4 electrode material. At a current density of 10 A / g, the capacity retention rate is 95.1% after 5000 cycles.

[0037] Example 2

[0038] This embodiment provides a method for preparing a ZIF-67 derived Co2VO4 material, comprising the following steps:

[0039] (1) 5.76 g of 2-methylimidazole was dissolved in 60 mL of deionized water to form solution A, and 874 mg of Co(NO3)2·6H2O and 15 mg of CTAB were dissolved in 30 mL of deionized water to form a uniform mixed solution B. Solution B was then quickly poured into solution A and stirred for 0.5 h. After centrifugation and washing, the solution was dried at 60 °C under vacuum for 8 h to obtain a ZIF-67 precursor.

[0040] (2) Disperse 30 mg of ZIF-67 precursor in 20 mL of anhydrous ethanol by ultrasonic for 10 min to obtain solution C; dissolve 23.59 mg of NH4VO3 in 5 mL of deionized water to obtain solution D; add solution D to solution C and stir for 30 s to obtain a suspension;

[0041] (3) The suspension obtained in (2) was poured into a 100 mL reactor and subjected to hydrothermal reaction at 90 °C for 2 h. The obtained product was washed by centrifugation and then dried under vacuum at 60 °C for 8 h.

[0042] (4) The reaction product obtained in (3) was heated to 250°C at a heating rate of 2°C / min for 1 h under N2 atmosphere to obtain Co2VO4;

[0043] The electrochemical performance of Co2VO4 prepared in Example 2 was tested using the same three-electrode test conditions as in Example 1. At a current density of 0.5 A / g, the specific capacity of Co2VO4 can reach 383.56 F / g. At a current density of 10 A / g, the capacity retention rate after 5000 cycles is 92.5%.

[0044] Example 3

[0045] This embodiment provides a method for preparing a ZIF-67 derived Co2VO4 material, comprising the following steps:

[0046] (1) 5.76 g of 2-methylimidazole was dissolved in 60 mL of deionized water to form solution A, and 874 mg of Co(NO3)2·6H2O and 15 mg of CTAB were dissolved in 30 mL of deionized water to form a uniform mixed solution B. Solution B was then quickly poured into solution A and stirred continuously for 0.5 h. After centrifugal washing, the mixture was dried at 60 °C under vacuum for 8 h to obtain a ZIF-67 precursor.

[0047] (2) Disperse 60 mg of ZIF-67 precursor in 50 mL of anhydrous ethanol by ultrasonication for 25 min to obtain solution C; dissolve 59.76 mg of NH4VO3 in 15 mL of deionized water to obtain solution D; add solution D to solution C and stir for 2 min to obtain a suspension;

[0048] (3) The suspension obtained in (2) was poured into a 100 mL reactor and subjected to hydrothermal reaction at 150 °C for 6 h. The obtained product was washed by centrifugation and then dried under vacuum at 60 °C for 8 h.

[0049] (4) The reaction product obtained in (3) was heated to 450°C under N2 atmosphere at a heating rate of 2°C / min for 4 h to finally obtain Co2VO4.

[0050] The electrochemical performance of Co2VO4 prepared in Example 3 was tested using the same three-electrode test conditions as in Example 1. At a current density of 0.5 A / g, the specific capacity of Co2VO4 can reach 332.74 F / g. At a current density of 10 A / g, the capacity retention rate after 5000 cycles is 93.2%.

[0051] Example 4

[0052] This embodiment provides a method for preparing a ZIF-67 derived Co2VO4 material, comprising the following steps:

[0053] (1) 5.76 g of 2-methylimidazole was dissolved in 60 mL of deionized water to form solution A, and 874 mg of Co(NO3)2·6H2O and 15 mg of CTAB were dissolved in 30 mL of deionized water to form a uniform mixed solution B. Solution B was then quickly poured into solution A and stirred for 0.5 h. After centrifugation and washing, the solution was dried at 60 °C under vacuum for 8 h to obtain a ZIF-67 precursor.

[0054] (2) Disperse 80 mg of ZIF-67 precursor in 55 mL of anhydrous ethanol by ultrasonication for 30 min to obtain solution C; dissolve 83.89 mg of NH4VO3 in 25 mL of deionized water to obtain solution D; add solution D to solution C and continue stirring for 3 min to obtain a suspension;

[0055] (3) The suspension obtained in (2) was poured into a 100 mL reactor and subjected to hydrothermal reaction at 180 °C for 8 h. The obtained product was washed by centrifugation and then dried under vacuum at 60 °C for 8 h.

[0056] (4) The reaction product obtained in (3) was heated to 550°C under N2 atmosphere at a heating rate of 2°C / min for 6 h to finally obtain Co2VO4.

[0057] The electrochemical performance of Co2VO4 prepared in Example 3 was tested using the same three-electrode test conditions as in Example 1. At a current density of 0.5 A / g, the specific capacity of Co2VO4 can reach 281.13 F / g. At a current density of 10 A / g, the capacity retention rate after 5000 cycles is 90.1%.

[0058] Therefore, the ZIF-67-derived Co2VO4 supercapacitor electrode material prepared in the present invention exhibits relatively high specific capacity and capacity retention rate, and has good application prospects.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it, that is, it does not mean that the present invention must rely on the above detailed methods to be implemented. It should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose of the technical solution of the present invention, which are all within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a ZIF-67 derived Co2VO4 supercapacitor electrode material, characterized in that: Using ZIF-67 as a template, Co2VO4 nanomaterials with the original morphology of ZIF-67 were prepared by hydrothermal and thermal treatment; The specific steps include: (1) 2-Methylimidazole was dissolved in deionized water to form solution A, and Co(NO3)2·6H2O and CTAB were dissolved in deionized water to form a uniform mixed solution B; then, solution B was quickly poured into solution A under stirring conditions, and stirring was continued for 0.5 h; after centrifugation and washing, the solution was vacuum dried at 60 °C for 8 h to obtain a ZIF-67 precursor; (2) Ultrasonic dispersion of ZIF-67 in anhydrous ethanol to obtain solution C; dissolving NH4VO3 in deionized water to obtain solution D; adding solution D to solution C and stirring continuously to obtain a suspension; (3) The suspension prepared in (2) was placed in a 100 mL reactor for hydrothermal reaction. The obtained product was washed by centrifugation and then dried at 60 °C under vacuum for 8 h. (4) heat treating the dried product obtained in (3) under a N2 atmosphere at a heating rate of 2°C / min to obtain Co2VO4; In step (2), the molar ratio of ZIF-67 to NH4VO3 is 1:1.5-2; In step (3), the temperature range of the hydrothermal reaction is 90 to 150° C., and the time of the hydrothermal reaction in step (3) is 2 to 5 hours; In step (4), the temperature range of the heat treatment is 250 to 450° C., and the time of the heat treatment in step (4) is 1 to 4 hours.

2. The method according to claim 1, characterized in that The concentration of 2-methylimidazole solute in solution A of step (1) is 96 mg / ml; the concentration of Co(NO3)2·6H2O solute in mixed solution B is 58.27 mg / ml, and the concentration of CTAB solute is 0.5 mg / ml.

3. The method according to claim 1, characterized in that The concentration of 2-methylimidazole solute in solution A of step (1) is 96 mg / ml; the concentration of Co(NO3)2·6H2O solute in mixed solution B is 58.27 mg / ml, and the concentration of CTAB solute is 0.5 mg / ml.

4. The method according to claim 1, characterized in that: In step (2), the ultrasonic time of ZIF-67 is 10 to 30 minutes.

5. The method according to claim 1, characterized in that: In step (2), the stirring time is 30 s to 3 min.

6. The Co2VO4 derived from ZIF-67 obtained by the preparation method according to claim 1 is used as a supercapacitor electrode material.

Citation Information

Patent Citations

  • Vanadium-based ZIF (Zeolitic Imidazolate Framework) porous material applied to cathode of lithium battery and preparation method of material

    CN108807998A

  • A method for preparing an electrode of ZIF-derived CoMoO4

    CN109243863A